2023
DOI: 10.3389/fchem.2023.1235437
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of novel silver and zinc oxide nanoparticles from Fusarium solani IOR 825 and their potential application in agriculture as biocontrol agents of phytopathogens, and seed germination and seedling growth promoters

Abstract: Introduction: Plant pathogenic microorganisms adversely affect the growth and yield of crops, which consequently leads to losses in food production. Metal-based nanoparticles (MNPs) can be a remedy to solve this problem.Methods: Novel silver nanoparticles (AgNPs) and zinc oxide nanoparticles (ZnONPs) were biosynthesized from Fusarium solani IOR 825 and characterized using Dynamic Light Scattering (DLS), Fourier Transform Infrared (FTIR) spectroscopy, Transmission Electron Microscopy (TEM), X-ray diffraction (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…showed no significant growth differences at concentrations of 624 and 312 µg/mL ( Figure 5 ). Trzcińska-Wencel et al [ 43 ] also studied ZnO nanoparticles biosynthesized from fungal extracts against various phytopathogens, including strains of genera Fusarium and Phoma . Using the poisoned plate method, they found that most Fusarium strains were not inhibited by the nanoparticles, while Phoma showed a 60% inhibition rate at 1000 µg/mL, similar to the obtained results in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…showed no significant growth differences at concentrations of 624 and 312 µg/mL ( Figure 5 ). Trzcińska-Wencel et al [ 43 ] also studied ZnO nanoparticles biosynthesized from fungal extracts against various phytopathogens, including strains of genera Fusarium and Phoma . Using the poisoned plate method, they found that most Fusarium strains were not inhibited by the nanoparticles, while Phoma showed a 60% inhibition rate at 1000 µg/mL, similar to the obtained results in the present work.…”
Section: Discussionmentioning
confidence: 99%